2016
DOI: 10.3310/hsdr04220
|View full text |Cite
|
Sign up to set email alerts
|

Determining the optimal model for role substitution in NHS dental services in the UK: a mixed-methods study

Abstract: BackgroundMaximising health gain for a given level and mix of resources is an ethical imperative for health-service planners. Approximately half of all patients who attend a regular NHS dental check-up do not require any further treatment, whereas many in the population do not regularly attend. Thus, the most expensive resource (the dentist) is seeing healthy patients at a time when many of those with disease do not access care. Role substitution in NHS dentistry, where other members of the dental team underta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 109 publications
1
19
0
Order By: Relevance
“…However, in a descriptive study which examined the attitudes of new patients to mid-level providers working independently to dentists, they found 98 percent of responding patients were satisfied with their mid-level provider care, and 80 percent attended a dental appointment within the next 12 months (43). This concurs with other studies, which found that patients who have a high degree of satisfaction with their experience with midlevel providers (11,39,(44)(45)(46).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in a descriptive study which examined the attitudes of new patients to mid-level providers working independently to dentists, they found 98 percent of responding patients were satisfied with their mid-level provider care, and 80 percent attended a dental appointment within the next 12 months (43). This concurs with other studies, which found that patients who have a high degree of satisfaction with their experience with midlevel providers (11,39,(44)(45)(46).…”
Section: Discussionsupporting
confidence: 92%
“…A review of international research literature that investigated the impact a specific type of mid-level provider (dental therapists) has on productivity and finances concluded their use does not increase practices' net revenues (34). However, in the UK, many of these factors related to the constraints within the existing system, rather than the performance of the mid-level provider per se (11). In the comparison of our study outcomes to other studies, it is important to consider that provider performance and costs may depend of the healthcare settings they are used in.…”
Section: Discussionmentioning
confidence: 99%
“…Business pressure means the cost-effectiveness of different remuneration models for FV application is likely to be of continued interest ( Birch, 2015 ) because this affects aspects of the model such as time, space and staff resources ( Brocklehurst et al, 2013b , Conquest et al, 2015 ). We have reported that, in terms of evidence-based practice, practitioner beliefs about effectiveness ( Elouafkaoui et al, 2015 ), clinical judgement relating to need, and patient preferences, seem to be somewhat stronger drivers than the available research evidence on its own ( Vander Schaaf et al ) How to best extend duties across the dental team is known to be a somewhat intractable problem ( Brocklehurst et al, 2013a ), but interesting research is seeking to understand how best to utilise the team to increase efficiency and lower costs ( Brocklehurst et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of legal issues and liabilities (Colvin et al, 2013) or incentives in remuneration systems (Brocklehurst et al, 2016) are examples of factors that are likely to influence collaboration between dentists and dental hygienists.…”
Section: Experimental Conditionmentioning
confidence: 99%